2017
DOI: 10.1080/10942912.2017.1315594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and rheological properties of water-extractable polysaccharides derived from okra (Abelmoschus esculentus L.)

Abstract: View related articles View Crossmark data Citing articles: 10 View citing articles Molecular characteristics and rheological properties of water-extractable polysaccharides derived from okra (Abelmoschus esculentus L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Some authors, in order to understand which chemical plays an important role in the antidiabetic activity of okra, are focused on study of okra polysaccharide and related characteristics. The structure of pectin in okra have investigated in several reports [79,80,81]. The recent work of Xu et al [81] reported molecular characteristics and rheological properties of water-extractable polysaccharides derived from okra ( Abelmoschus esculentus L.): the proportions of galacturonic acid and monosaccharides in the refined polysaccharides were 62.47% and 13.47%, respectively.…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors, in order to understand which chemical plays an important role in the antidiabetic activity of okra, are focused on study of okra polysaccharide and related characteristics. The structure of pectin in okra have investigated in several reports [79,80,81]. The recent work of Xu et al [81] reported molecular characteristics and rheological properties of water-extractable polysaccharides derived from okra ( Abelmoschus esculentus L.): the proportions of galacturonic acid and monosaccharides in the refined polysaccharides were 62.47% and 13.47%, respectively.…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
“…The structure of pectin in okra have investigated in several reports [79,80,81]. The recent work of Xu et al [81] reported molecular characteristics and rheological properties of water-extractable polysaccharides derived from okra ( Abelmoschus esculentus L.): the proportions of galacturonic acid and monosaccharides in the refined polysaccharides were 62.47% and 13.47%, respectively. Some reports have mentioned that okra polysaccharides are associated to several bioactivities linked to diabetes management, i.e., hypoglycemic activity, and are indicated as novel immunomodulators [37,82,83], in addition to others [84,85,86,87,88].…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
“…Furthermore, the main bioactive component of okra mucilage is okra polysaccharide, which is reported to be comprising of pectic polysaccharides [10]. Meanwhile, the compositions of waterextractable polysaccharides were reported to be galacturonic acid, rhamnose, arabinose, xylose, mannose, galactose, glucose, xylan, starch, and uronic acid [11,12]. In addition, okra polysaccharides have been reported for their antioxidant activity, immunomodulatory activity, ability to improve metabolic disorders and intestinal function, hypoglycemic activity, and antifatigue activities.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of pectin was performed according to M-hydroxydiphenyl method with galacturonic acid (GalA) as the standard. [6] High performance liquid chromatography analysis Ferulic acid and 4-VG were measured using high performance liquid chromatography (HPLC) equipped with an ultraviolet detector at 230 nm. Samples were degassed, passed through a 0.45 μm filter, and analyzed using Atlantis C18 column (250 mm × 4.6 mm, 5 μm, Waters., USA).…”
Section: Physicochemical Indicesmentioning
confidence: 99%
“…[1,2] Okra polysaccharides include galactose, galactan, araban, and pectin, [3,4] which has been widely used as food additive and nutrient supplement. [5] Water-extractable okra polysaccharide is shown having very good viscoelasticity, [6] which makes it a good thickening and suspension agent. In addition, okra polysaccharide can provide special flavor and nutrition to beverage.…”
Section: Introductionmentioning
confidence: 99%